Aqueous Photo-Living Radical Polymerization of Sodium Methacrylate Using a Water-Soluble Nitroxide Mediator. (12th June 2012) - Yoshida, Eri
Abstract : The aqueous photo-living radical polymerization of sodium methacrylate (NaMA) was attained using 2, 2′-azobis{ 2-methyl- N -[1, 1-bis(hydroxymethyl)-2-hydroxyethyl]-propionamide} (V-80) as the initiator and 4-hydroxy-2, 2, 6, 6-tetramethylpiperidine-1-oxyl (HTEMPO) as the mediator in the presence of (4-fluorophenyl)diphenylsulfonium triflate (FS). The polymerization was carried out in water at room temperature by irradiation using a high-pressure mercury lamp. Whereas the polymerization by V-80 and/or FS in the absence of HTEMPO produced polymers with very high molecular weights and broad molecular weight distributions, the HTEMPO-mediated polymerization provided still lower-molecular-weight distributions using both V-80 and FS. The first-order time-conversion plots had an induction period up to 2.5 h; however, they thereafter showed a linear increase. The conversion-molecular weight plots also exhibited a linear correlation. A linear correlation was also obtained for the plots of the molecular weights versus the reciprocal of the initiator concentration. Based on these three correlations, it was found that the HTEMPO-mediated photopolymerization proceeded by a living mechanism.